5, 5'-Indigodisulfonic acid as an efficient catalyst for the synthesis of 2, 3-dihydroquinazolinone derivatives. Issue 13 (18th July 2022) - Liu, Cheng-Hang; Wang, Qiong; Xu, Zenglai; Li, Dongling; Zheng, Yuhong
Abstract: An efficient protocol for the synthesis of 2, 3-dihydroquinazolinone derivatives from substituted 2-aminobenzamides and carbonyl analog catalyzed by the natural-based 5, 5'-indigodisulfonic acid has been developed with good to excellent yields. Compared to the reaction conditions reported before, the use of eco-friendly and recyclable catalysts and mild reaction conditions are the major advantages of the present method. Graphical Abstract: UF0001